THE ACTS OF ACADEMIC DISHONESTY IN A CHRISTIAN SCHOOL - Anditya, Novia Hoki; Panggabean, Meicky S; Hidayat, Dylmoon (JOHME: Journal of Holistic Mathematics Education, 2018)
The problem of academic dishonesty is a common problem in academia, but it is a serious problem that needs to be solved. Academic dishonesty, as the opposite of academic integrity, is the condition where students carryout their academic work (i.e., assignments and tests) dishonestly. From a Christian perspective, when students truly know Christ and have integrity in their lives, problems like academic dishonesty should not exist because students are supposed to live out their Christian values. In the brokenness of this world, these problems still happen even in Christian academic institutions. The purpose of this paper is to examine the factors causing academic dishonesty and other problems resulting from academic dishonesty, determine how to deal with acts of academic dishonesty, and suggest some ways to prevent academic dishonesty. To deal with academic dishonesty, the authors suggest some ways that are adapted from the PDCA (Plan-Do-Check-Action) theory, also known as The Deming Cycle. Ultimately, helping students act with academic integrity, instead of with academic dishonesty, requires the involvement of everyone in the school, including students and parents.  BAHASA INDONESIA ABSTRACT: Masalah ketidakjujuran akademik adalah masalah umum yang terjadi dalam bidang akademik, tapi masalah ini adalah masalah serius yang harus diselesaikan. Ketidakjujuran akademik adalah lawan dari integritas akademik yaitu kondisi ketika siswa mengerjakan berbagai aktivitas mereka di bidang akademik (seperti tugas dan ujian) secara tidak jujur. Dari perspektif Kristen, ketika siswa mengenal Kristus dan memiliki integritas dalam hidup mereka, masalah ketidakjujuran akademik seharusnya tidak pernah ada lagi dalam sekolah Kristen, karena siswa seharusnya hidup berdasarkan nilai tersebut. Kenyataannya dalam kejatuhan dunia ini, masalah ketidakjujuran akademik masih terjadi bahkan di institusi pendidikan Kristen. Kajian literatur ini memiliki tujuan untuk menguji berbagai faktor pernyebab masalah ketidakjujuran akademik, masalah lain akibat perbuatan ketidakjujuran akademik, bagaimana menangani masalah ketidakjujuran akademik, dan beberapa saran untuk mencegah masalah ketidakjujuran akademik. Untuk menangani masalah ketidakjujuran akademik, penulis menyarankan beberapa langkah yang diambil dari teori PDCA (Plan-Do-Check-Action) yang juga dikenal sebagai siklus Deming. Dari semuanya itu, mencegah kemungkinan yang membuat siswa melakukan tindakan ketidakjujuran akademik perlu dilakukan oleh guru, sekolah, dan semua orang yang terlibat dalam dunia akademik termasuk orang tua.